THE BELT AND ROAD INITIATIVE: DYNAMICS FOR THE LATIN AMERICA AND THE CARIBBEAN REGION - Tripathi, Anurag; RL, Abhishek; Teja, Arun (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2023)
The Belt and Road Initiative (BRI) is increasingly turning out to become a global endeavor and has recently been extended to Latin America and the Caribbean (LAC) region. The diversity in the makeup of the nation-states in the region poses several challenges concerning the region's association with the BRI. For instance, Venezuela has borrowed heavily from China while being mired in economic troubles. The Venezuelan example serves as a caution to others as well as China on the intricacies of debt management and lending. This paper aims to study the challenges and risks arising from the Belt and Road Initiative extending to Latin America and the Caribbean region. This paper also tries to analyses as to whether a win-win outcome can be achieved for both China and the LAC nation-states and as to what China seeks from the region. An attempt has been made to evaluate the role that the global environment might play in this evolving relationship between China and the LAC nation-states. The paper also analyse the post pandemic BRI investment in the LAC region.